2020
DOI: 10.1155/2020/5794187
|View full text |Cite
|
Sign up to set email alerts
|

Chondrotoxicity of Local Anesthetics: Liposomal Bupivacaine Is Less Chondrotoxic than Standard Bupivacaine

Abstract: Objective. The purpose of this study is to determine whether (1) liposomal bupivacaine is chondrotoxic; (2) the chondrotoxicity of liposomal bupivacaine differs from standard bupivacaine; and (3) chondrotoxic effects are time dependent. Materials and Methods. We obtained 72 10 mm articular cartilage plugs from 12 fresh bovine distal femoral knee joints and exposed them to either saline, 0.5% bupivacaine, or liposomal bupivacaine for either 30 or 90 minutes. Twenty-four hours after treatment, chondrocyte viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The condition NL-TGF 10 had even a better effect in term of proliferation compared to NL-TGF 100. Moreover, liposomes could potentially decrease the cytotoxicity of active molecules towards chondrocytes as shown by Farmer et al [ 31 ]. In their study, they demonstrated that the bupivacaine loaded in liposomes (EXPAREL ® ) is less chondrotoxic than standard bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…The condition NL-TGF 10 had even a better effect in term of proliferation compared to NL-TGF 100. Moreover, liposomes could potentially decrease the cytotoxicity of active molecules towards chondrocytes as shown by Farmer et al [ 31 ]. In their study, they demonstrated that the bupivacaine loaded in liposomes (EXPAREL ® ) is less chondrotoxic than standard bupivacaine.…”
Section: Discussionmentioning
confidence: 99%